Nano-Neurogenesis for CNS Diseases and Disorders - Tiwari, Sneham; Kaushik, Ajeet (Frontiers in Nanotechnology, 2022)
Neurogenesis encompasses the formation and development of neurons in the mammalian brain, mainly occurring in hippocampus and olfactory system. This process is rapid, accurate and very sensitive to the external stressors including environment, diet, age, anxiety, stress, depression, diet, and hormones. The range of stressors is big and directly impacts the generation, maturation and migration, efficacy, and myelination of the neuronal cells. The field of regenerative medicine focusses on combating the direct or indirect effects of these stressors on the process of neurogenesis an ensures increased general and neuronal communications and functioning. Understanding the deep secrets of the brain signaling and devising ways to increase drug availability is tough, considering the complexity and intricate details of the neuronal networks and signaling in the CNS. It is imperative to understand this complexity and introduce potent and efficacious ways to combat diseases. This perspective offers an insight how neurogenesis could be aided by nanotechnology and what are the plausible nanomaterial available to culminate neurogenesis related neurological disorders. The nanomaterials are promising as they are minute, robust, effective and help in diagnostics and therapeutics like drug delivery, maturation and neuroprotection, neurogenesis, imaging, and neurosurgery.